The recent Italian vaccination law and the role of Local Health Authorities: the case of LHA Roma 1. (13th November 2019) - Frisicale, E M; Miceli, M T; Romagnuolo, M R; Agostinacchio, R; Angelis, F De; Gangere, F; Giudiceandrea, B; Rombolà, A M; Spadea, A; Goletti, M
Abstract: Issue/problem: The increase of vaccine hesitancy is leading to decrease vaccination coverage. In Italy, a new vaccination law was approved in July 2017 to contrast the spread of preventable infections. 10 vaccines became mandatory for children and unaccompanied foreign minors aged 0-16 and provided for free according to the national immunization schedule for each birth cohort. Being vaccinated is now required to attend schools and kindergartens even if a ban for students aged 0-6 or a fine for the other are previewed. Description of the problem: According to the law, in Lazio Region, a web platform was realized in May 2018 in order to permit schools to update the list of their pupils. Medical doctors from LHAs had to evaluate continuously the updated lists, verifying the vaccination status of each student in order to approve their enrolment at schools or to recall parents providing counseling about vaccination. Results: From August 2018 to March 2019 schools settled in the area of LHA Roma 1 registered 121.687 pupils (among those 105.720 pupils were also resident in the area of LHA Roma 1). After a preliminary check within data already present in the regional vaccination registry, around 30 healthcare operators, from the 6 healthcare districts of LHA Roma 1, were widely involved in order to evaluate pupils' vaccination status. The number of evaluations decreases in the same period from 19.634 to 4921, but 4908 out of these 4921 were pupils not found in the regional vaccination registry, probably for errors in the registration of personal data such as the fiscal code. Some students' families received vaccination counseling. Lessons: The web platform realization was an innovative way to monitor vaccination status: it facilitates a further collaboration among schools and LHAs in order to guarantee health in community and to increase awareness about vaccinations and their benefits. A great involvement of schools and healthcare operators was observed. Key messages: Although some problems such as pupils not found in the regional vaccination registry persist, the way of working in a collaborative way addressing community troubles is clearly traced. Technology and information systems help community services in monitoring and improving health outcomes. Their use has to be improved and promoted.